The Importance of Strength Typology (ST) 30 in Compilation of Personal Curriculum for Homeschooling Partners - Lukman Hakim; Maria Veronika Roesminingsih; Widodo Widodo (Edukasi, 2023)
Another online-based assessment that teachers can useto map their talents is Strength Typology-30 (ST-30). ST-30 is a device that can map a person's potential based on theactivities he does. The purpose of this research is to analyze the benefits of the Strength Typology (ST) 30 in thepreparation of the personal curriculum of Homeschooling PKBM FIB Malang partners, because the reare still many homeschoolers experiencing difficultiesin compiling their personal curriculum, so bymaking observations in advanceit is hoped that the families of homeschoolers will be morehelpful. This research was conducted using qualitative research methods to answer research problems in order to describe phenomena in the field. The data collection techniques used were observation, interview, and documentation techniques, which were then analyzed using Miles and Huberman's data analysis techniques, namelydata collection, data reduction, data presentation and drawing conclusions. The results of the study show that there are benefits or conveniences if before compiling a personal curriculum for homeschooling in which there are plans for face-to-face activities, tutorials and self-study for all core subjects, choicesas well as skills and empowerment, a Strength Typology (ST) 30.